2019
DOI: 10.18632/oncotarget.26592
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of MSMB promoter region gene polymorphism to early-onset prostate cancer risk in Mexican males

Abstract: Sexually transmitted infections and its contribution to prostate cancer (PC) development have been relevant in different populations. MSMB gene polymorphism (rs10993994) has exhibited an association both with PC as well as the susceptibility to sexually transmitted infections. Hitherto, these conditions have been not studied in Mexico yet, neither if sexually transmitted infections could modify the MSMB and PC association. Herein, socio-demographic features, sexually transmitted infections records, the reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, genome-wide association studies have reported the link between a polymorphic variant (rs10993994; C > T ) located in the MSMB promoter region and higher PC risks due to the downregulation of the MSMB [ 17 , 18 ]. In addition, TT genotype shows associations with the highest susceptibility to develop PC than CC/CT genotypes [ 19 ]. Despite the fact that MSMB may be evaluated as a disease genetic risk factor, the role of MSMB in stratification of clinically significant PC cases with rising PSA after negative transrectal systematic prostate biopsy is still unknown [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, genome-wide association studies have reported the link between a polymorphic variant (rs10993994; C > T ) located in the MSMB promoter region and higher PC risks due to the downregulation of the MSMB [ 17 , 18 ]. In addition, TT genotype shows associations with the highest susceptibility to develop PC than CC/CT genotypes [ 19 ]. Despite the fact that MSMB may be evaluated as a disease genetic risk factor, the role of MSMB in stratification of clinically significant PC cases with rising PSA after negative transrectal systematic prostate biopsy is still unknown [ 20 ].…”
Section: Introductionmentioning
confidence: 99%